Alterações químicas e biológicas em solo de área de mineração de carvão submetido a diferentes cultivos - Santos, Daiane Carvalho dos (2006)
The coal deposits in Brazil comprehend 32 billion tons, being 89% in Rio Grande do Sul. Even though it is an important energy resource, the coal extraction, processing and use create great soil transformation, specially the open pil mining, causing relevant physical, chemical and biological properties alterations. The re-vegetation aims to re-establish the area original characteristics, avoid erosion process allowing the soil restructure. This work intends to evaluate the chemical and biological attribute changes in the recovered soil according to vegetal covering from different species. The study was developed in a recovered coal mining soil in Candiota - RS, with a block lining at random, with four repetitions, with the following treatments: Hemartria altíssima, Cynodon dactilum, Paspalum lourai, Combination Hemartria altíssima + Arachis pintoi, Combination Cynodon dactilum + Arachis pintoi and Combination Paspalum lourai + Arachis pintoi. The results were compared with analyses of a natural soil adjacent to the mining area. The results allowed the following conclusions: the Hemartria altíssima + Arachis pintoi cultivations in the recovered soil presented the higher dry material productions, with amounts similar to the culture productivity in natural conditions; the nutrients and lime applications in the cultivation area, in general terms, increased the electrical conduction and changeable sodium amount, these amounts presented a decrease as the time went by turning equalized to ones observed in natural soil; after 562 days of different cultivation implantation, the levels of organic carbonic and total nitrogen are much lower than ones observed in natural soil, adjacent to the mining area; the treatments with Hemartria altíssima, Cynodon dactilum, Paspalum lourai and Cynodon dactilum + Arachis pintoi, maintained the microbial biomass carbon levels, after 380 days of cultivation implantation, higher than observed in natural soil; after 562 of cultivation the microbial biomass nitrogen levels continued lower than natural soil determined levels; the microbial activity in all studied cultivation became higher with the soil recovering period; the activity with Cynodon dactilum + Arachis pintoi, cultivation, after 562 days of experiment implantation was similar to natural soil microbial activity and after 562 days of cultivation, the CO2 intense liberation, in all treatments, increased the qCO2 to amounts higher than observed in natural soil. PDF Creator